Pemanfaatan Teknologi Informasi dalam Simulasi Perhitungan Harga Pokok Penjualan dan Keuntungan Usaha bagi Tenan dan Mitra Usaha di Provinsi Sumatera Barat - Rayna Kartika; Dian Yuni Anggraeni; Annisaa’ Rahman; Denny Yohana; Verni Juita; Rita Rahayu; Amsal Djunid; Syahril Ali; Rinaldi Munaf (Warta Pengabdian Andalas, 2020)
The community services activity in utilizing information technology is to assist and simulate tenants and partner to calculate cost of goods sold. One of the reasons is that most of MSMEs tenant and partners are not from Accounting background. The purpose of this activity was to create a comprehensive knowledge about COGS report and profit calculation based on their business sectors. In conducting business activities, both individuals and business entities, the preparation of financial statements is very crucial to get financing access. The financial statements are the principal or the end result of an accounting process that is material for information for the stakeholders. Financial statements are also an indicator of the success of a business activity. MSMEs have a vital role in the development of the economic wheels of a region, therefore, if MSMEs can define their financial conditions well, then business actors can make strategic decisions to maintain and increase the profitability of their businesses.